Conceptualizing American Attitudes toward Immigrants’ Dual Loyalty - DeLisi, Matt (Socius, 2016)
The social issue of immigrants’ dual loyalty figures prominently in the 2016 U.S. presidential primaries, yet little is known about Americans’ views on the subject. Drawing on data from a nationally representative telephone survey, the authors specifically explored nonimmigrant Americans’ attitudes toward immigrants’ dual loyalty. The results show that attitudes toward this dual loyalty are informed by multiple boundary-making processes, including the extent to which respondents strongly believe that immigrants should celebrate American values and traditions and share their vision of America, that immigration should be restricted as much as possible, and that American influence in the world is important